Global Trade Restrictions during Covid-19 Pandemic - Riady, Riady; Fita, Gia Ayu; Fiqhi Utami, Andi Nur; B. Tahawa, Taufik Hidayat (International Journal of Educational Research & Social Sciences, 2021)
In early 2020 with the emergence of the corona virus which originated in China, became a threat to every country because it caused many victims to die. The massive spread of the corona virus globally throughout the world has an impact on every country in various sectors, be it social, political, economic, tourism, or domestic and global trade sectors. This is because many countries have issued policies restricting access to the country not only for the public, but also for certain products originating from other countries with the aim of minimizing the growing circulation of the corona virus. Of the many countries, including Indonesia, felt the impact of this case, especially in the global trade sector because it caused delays in various types of products that should have been exported to various countries due to restrictions on the acceptance of imported goods by certain countries through policies issued supported by the World Trade Organization's record stating that During the Covid-19 pandemic, there were many countries that implemented global trade restrictions.